Molecular mechanisms of resveratrol as chemo and radiosensitizer in cancer - Cotino-Nájera, Sandra; Herrera, Luis A.; Domínguez-Gómez, Guadalupe; Díaz-Chávez, José (Frontiers in Pharmacology, 2023)
One of the primary diseases that cause death worldwide is cancer. Cancer cells can be intrinsically resistant or acquire resistance to therapies and drugs used for cancer treatment through multiple mechanisms of action that favor cell survival and proliferation, becoming one of the leading causes of treatment failure against cancer. A promising strategy to overcome chemoresistance and radioresistance is the co-administration of anticancer agents and natural compounds with anticancer properties, such as the polyphenolic compound resveratrol (RSV). RSV has been reported to be able to sensitize cancer cells to chemotherapeutic agents and radiotherapy, promoting cancer cell death. This review describes the reported molecular mechanisms by which RSV sensitizes tumor cells to radiotherapy and chemotherapy treatment.